Literatur Review: Sejarah Terciptanya Operasi Sistem ANDROID Sebagai Pion Multimedia Umat Manusia - Sugiharto, Gusti Aditya Muzaky (Jurnal Pelita Teknologi, 2022)
Android is one of the most popular mobile operating systems (OS) in the world. This operating system was first released in 2008 and has undergone rapid development over the years. One of the factors that contributed to the success of Android is its support for multimedia. The Android operating system has demonstrated its ability to run a variety of multimedia applications, such as music players, video players, cameras, and photo galleries. In addition, Android has become a pioneer in multimedia for humanity because of its ability to deliver high-quality and easy-to-use multimedia content. As the author of this literature review, I hope that the results of this study can provide a deeper understanding of the role of Android as a pioneer in multimedia for humanity. I also hope that this study can contribute to the understanding of the history of Android and its continued relevance today.